La investigacion en campos de agricultores sobre frijol tapado en Costa Rica - Araya Villalobos, Rodolfo; González M, W. (International Center for Tropical Agriculture, 1987)
From the most important bean-growing areas in Costa Rica, 5 representative locations were selected; a random sampling of 44 farms was conducted to find out why farmers prefer the covered bean system and its main agronomic characteristics. Farmers who used this system were based on characteristics such as low production costs, less risk for invested capital, traditional activities that allow for producing the beans that are going to be consumed during the yr and sell the remaining, less labor requirement, and the use of highly steeped land. A total of 38 percent of the farmers who engaged in the project had losses on beans planted in this system; 9 percent had profits between 40 and 80 percent, and 62 percent had profits varying between 100 and 502 percent. (CIAT)